Strengths-Based Leadership and Turnover Intention: The Roles of Felt Obligation for Constructive Change and Job Control - Chu, Xixi; Ding, He; Zhang, Lihua; Li, Zhuyi Angelina (Frontiers in Psychology, 2022)
This study draws on the substitutes for leadership theory to investigate the association of strengths-based leadership with turnover intention and the mediational role of felt obligation for constructive change and the moderating role of job control in the linkage. Data were collected using a three-wave survey from a sample of 317 employees working in a variety of enterprises in China. Multiple regression analyses with bootstrapping procedure was utilized to examine the proposed hypotheses. Results showed that strengths-based leadership negatively relates to turnover intention, and felt obligation for constructive change partially mediates the relationship between strengths-based leadership and turnover intention. Furthermore, this study also found that job control negatively moderated the indirect relationship between strengths-based leadership and turnover intention via felt obligation for constructive change.